2019
DOI: 10.1111/btp.12738
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal networks in tropical forest fragments: Area effects, remnant species, and interaction diversity

Abstract: Seed dispersal interactions involve key ecological processes in tropical forests that help to maintain ecosystem functioning. Yet this functionality may be threatened by increasing habitat loss, defaunation, and fragmentation. However, generalist species, and their interactions, can benefit from the habitat change caused by human disturbance while more specialized interactions mostly disappear. Therefore, changes in the structure of the local, within fragment, networks can be expected. Here we investigated how… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…Our results contribute to this body of work, indicating that LH conservation and rewilding could slow down compositional change by filtering out the arrival of new species into communities. In the context of tropical forests, it is also noteworthy that the combined effects of climate change and land use are contributing to tree loss, forest functional changes and the emergence of fire, leading to a process of increasing faunal and floristic savannization (Alroy, 2017;Emer et al, 2020;Sales et al, 2020;Staal et al, 2020). LH might contribute to decelerate such process by decelerating compositional change and filtering against invasive species and life-forms typical of savanna-like forests.…”
Section: Large Herbivores Partially Buffer Against Directional Compos...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results contribute to this body of work, indicating that LH conservation and rewilding could slow down compositional change by filtering out the arrival of new species into communities. In the context of tropical forests, it is also noteworthy that the combined effects of climate change and land use are contributing to tree loss, forest functional changes and the emergence of fire, leading to a process of increasing faunal and floristic savannization (Alroy, 2017;Emer et al, 2020;Sales et al, 2020;Staal et al, 2020). LH might contribute to decelerate such process by decelerating compositional change and filtering against invasive species and life-forms typical of savanna-like forests.…”
Section: Large Herbivores Partially Buffer Against Directional Compos...mentioning
confidence: 99%
“…Tropical rainforests are subjected to unprecedented anthropogenic pressures that compromise their integrity and erode their diversity. Tree loss, widespread defaunation, changes in the functional structure of interactions and the emergence of fire threaten to drive many of such hyper-diverse ecosystems into a nonlinear process of floristic and faunal savannization (Alroy, 2017;Emer et al, 2020;Galetti et al, 2021;Sales et al, 2020;Staal et al, 2020). To halt the ecological meltdown of these hyper-diverse ecosystems, effective conservation and restoration measures are required to preserve the diversity in both old-growth and secondary tropical forests (Rozendaal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, forest loss can act as an important selective force, filtering frugivorous birds with specific phylogenetic and functional features, and thus interfering in the seed dispersal networks (Peña et al, 2020). In particular, recent studies reported significant changes in network structure (e.g., higher nestedness and lower modularity) after forest loss in Atlantic forest sites (Emer et al, 2020;Marjakangas et al, 2020) or changes in bird functions in deforested landscapes (Coster et al, 2015). Here, we found highly simplified seed-dispersal networks with only a few pairs of interacting species, whose structural properties have been depleted due to the loss of forest cover in these human-modified landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, species homogenization in more disturbed landscapes can concentrate interactions within some dominant species in the system, reducing interaction evenness (Rodewald et al, 2014). Similarly, the loss of species or decreasing species abundance in smaller forest fragments can affect the number of links per species by reducing the number of partners available for the interactions to occur (Muñoz et al, 2017;Emer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat fragmentation is one of the most important drivers of the decline in species diversity ( Dirzo et al., 2014 ; Haddad et al., 2015 ; Cao and Zhang, 2022 ), which may trigger cascading effects on ecological networks ( Taubert et al., 2018 ; Peters et al., 2019 ). In most remnant habitat patches, mutualistic networks for animal-mediated pollination and seed dispersal are disrupted by species loss ( Schupp et al., 2017 ; Grass et al., 2018 ) and affected by the size and quality of habitat patches ( Spiesman and Inouye, 2013 ; de Bomfim et al., 2018 ; Emer et al., 2019 ). Compared with large habitat patches, small habitat patches are unable to support the survival of most large-bodied species owing to their lower food quality and greater interspecific competition ( Hart et al., 2017 ; Ferretti and Fattorini, 2021 ).…”
Section: Introductionmentioning
confidence: 99%